Efficacy of the Combination of Teriparatide and Denosumab in the Treatment of Postmenopausal Osteoporosis: A Meta-Analysis - Sun, Yang; Li, Yue; Li, Jiangbi; Xie, Xiaoping; Gu, Feng; Sui, Zhenjiang; Zhang, Ke; Yu, Tiecheng (Frontiers in Pharmacology, 2022)
Aim: Evidence on the efficacy of combination treatment of teriparatide and denosumab for osteoporosis remains controversial. We aim to compare the efficacy between the combination treatment and monotherapy among patients with postmenopausal osteoporosis. Methods and results: We systematically searched PubMed, EMBASE, the Cochrane Library, and Web of Science up to 26 January 2022, for relevant studies. This meta-analysis reviewed all randomized controlled trials (RCTs) that reported on the combination treatment of teriparatide and denosumab in patients with postmenopausal osteoporosis. The articles were examined individually by two reviewers, and the relevant data was extracted. We combined weighted mean difference (WMD) for bone mineral density (BMD) using random- or fixed- effect models and conducted subgroup analyses. Sensitivity analyses were performed, and possible publication bias was also assessed. Overall, combination treatment enhanced the mean percent change of bone mineral density in lumbar spine than monotherapy (WMD = 2.91, 95%CI: 1.983.83; p = 0.00). And, combination treatment has been beneficial for enhancing the mean percent change of BMD in hip (WMD = 3.19, 95%CI: 2.25∼4.13; p = 0.00). There was no significant difference between combination treatment and monotherapy in terms of the adverse events (RR = 0.81, 95%CI: 0.45∼1.45; p = 0.472). Conclusion: The meta-analysis indicates that combination treatment led to greater BMD at the lumbar spine and hip in comparison to monotherapy, without an increased incidence of adverse events. Systematic Review Registration: (https://inplasy.com/), identifier (Inplasy Protocol 2734).